ANALISA SUSEPTIBILITAS MAGNETIK DAN KANDUNGAN LOGAM BERAT PADA TANAH PERKEBUNAN KELAPA SAWIT - Marisayani Hutauruk; Salomo Sinuraya (Universitas Riau, 2020)
The study of soil carried out from oil palm plantation soils at Garuda sakti street, Tapung, Kampar, Riau has been implemented since November 2019 to March 2020. This study aims to determine magnetic susceptibility, mass susceptibility, magnetic degree and to identify soil compositions and the content of heavy metals in the soils and to analyse the influence of content of heavy metals to the magnetic susceptibility. The samples were taken about one hundred points, then the samples were dried, cleaned, mashed and sifted. Magnetic susceptibility was measured using the Probe Magnetic Pasco PS-2162. Magnetic particles were separated from samples using the NdFeB magnet and identification of soil composition and the content of heavy metals were carried out using the XRF. The result shows that the value of magnetic susceptibility, mass susceptibility, magnetic degree are fluctuated and the compositon of the soils are Mg, Al, Si, P, K, Fe, Ca, Ti, V, Cr, Mn, Ni, Zn S, Cl, Co, Cu, Ga, Ge, As, Br, Rb, Sr, Y, Zr, Nb, Ag, Eu, Re and Pb and proved that soil has been contaminated by heavy metals such as V, Cr, Al, Fe, Ti and Sr from the soils until increase the Magnetic susceptibility of that soils.